PEMBERDAYAAN EKONOMI MASYARAKAT DI PONDOK PESANTREN DALWA BERDASARKAN MODEL EVALUASI SUMATIF CIPP - Laili, Yunita Nur; Zaki, Irham (Jurnal Ekonomi Syariah Teori dan Terapan, 2020)
Pondok pesantren is an institution that can contribute to empowering the community's economy through its business units. The effort was apparently carried out by Pondok Pesantren DALWA. This institute has 14 businesses, but not all of them have professional management, there are a hotel, mart, tour and travel, bread, and fried chicken. This research uses a summative evaluation model. It has four components are context, input, process, product. This model will report the reason, implementation, and result of empowerment. The purpose of this research was to analyze the model of community economic empowerment in the league. The research method is qualitative. Data collected through observations, interviews and documents. The data is validated by the triangulation of sources and techniques. The result showed the reason for empowerment because of independence, reliance, and da?wah. The program gives priority to male are competent, sincere, and amanah. This program consists of awareness, capacity, and making efficient use based on Islam. It is very useful for individual ability, effort, environment, and league. All of these empowerment cause positive impact to pesantren and societyKeywords: Summative evaluation model, the community economic empowerment, Pondok pesantren Darullughah Wadda?wah